Israel : Detailed Assessment of IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2012)
Israel's compliance with International Organization of Securities Commissions' objectives and Principles of Securities Regulation has been assessed. The regulatory regime is well developed and in most respects is comparable with that of major jurisdictions. For the most part, it is compliant with international standards and regulation, and oversight by the Israel Securities Authority is robust and effective. With regard to the regulation of broker dealers, there is a significant gap in the coverage of the regulatory regime.